Use of E-Commerce in Increasing Sales of Small and Medium-Sized Micro Enterprises (MSMEs) Boutiques is Amid Pandemic Covid-19 - Mohammad Imam Sufiyanto; Shalehoddin (Program Studi S3 Ilmu Manajemen, 2022)
The Covid-19 pandemic struck Indonesia and also the rest of the world, which has a huge impact on the Micro, Small, and Medium Enterprises (MSMEs). It is necessary to have a big movement to revive the economic passion in Indonesia, especially MSMEs, one of which is by utilizing e-commerce. E-Commerce is one of the means in the process of buying and selling products produced with a system that includes the use of the web online. The boutique is a fashion store that sells a variety of high-quality and exclusive clothing and accessories, customers can directly view the products being sold, register personal information, make orders, pay for goods. E-Commerce is created using the PHP programming language and MySQL database, using the Web Modeling Language (WebML) methodology. It was obtained that the E-Commerce data presented can increase the value of sales in the covid-19 pandemic with the use of E-Commerce makes it easier for consumers to choose items to be consumed or used without face-to-face or meeting between sellers and buyers. The online process is much more efficient compared to visitors coming directly to the store. Keywords: â€œE-Commerceâ€, â€œWeb Modeling Language (Web ML).